Single-cell imaging reveals efficient nutrient uptake and growth of microalgae darkening the Greenland Ice Sheet - Laura Halbach; Katharina Kitzinger; Martin Hansen; Sten Littmann; Liane G. Benning; James A. Bradley; Martin J. Whitehouse; Malin Olofsson; Rey Mourot; Martyn Tranter; Marcel M. M. Kuypers; Lea Ellegaard-Jensen; et al. (Nature Communications)
Abstract Blooms of dark pigmented microalgae accelerate glacier and ice sheet melting by reducing the surface albedo. However, the role of nutrient availability in regulating algal growth on the ice remains poorly understood. Here, we investigate glacier ice algae on the Greenland Ice Sheet, providing single-cell measurements of carbon:nitrogen:phosphorus (C:N:P) ratios and assimilation rates of dissolved inorganic carbon (DIC), ammonium and nitrate following nutrient amendments. The single-cell analyses reveal high C:N and C:P atomic ratios in algal biomass as well as intracellular P storage. DIC assimilation rates are not enhanced by ammonium, nitrate, or phosphate addition. Our combined results demonstrate that glacier ice algae can optimise nutrient uptake, facilitating the potential colonization of newly exposed bare ice surfaces without the need for additional nutrient inputs. This adaptive strategy is particularly important given accelerated climate warming and the expansion of melt areas on the Greenland Ice Sheet.